(untitled) (Mwanga wa Lugha, 2018)
Translation is a complex exercise that involves not only transfer of meaning of linguistic aspects of translated texts but more importantly their literary aspects. This means that for a translator come up with the translated text that meets the knowledge, expectations and values of the target audience they must consider their historical and geographical contexts. This paper examined the plays written by Kithaka wa Mberia in Kiswahili and translated in English with a view by the writer to reach a wider audience. We have assessed the themes presented, linguistic and stylistic devices employed and the characters presented to see whether the knowledge, expectations and values of the target audience are met. Given that these texts are originally written in Kiswahili, it was important to see how the translator conveys the message to the wider audience targeted by the choice of use of English language. In our analysis we employed the Skopos theory of translation which focuses on translation as a purposive activity intended for a particular audience. The conclusion is that the translated texts have not to a great extent conveyed the intended message to the audience targeted as the translators focused mainly on the linguistic equivalents and to a large extent failed to meet the knowledge, expectations and values of the wider audience targeted.